2023
DOI: 10.1186/s40659-023-00431-8
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid induces sarcopenia associated with decreased protein synthesis and autophagic flux

Abstract: Background Skeletal muscle generates force and movements and maintains posture. Under pathological conditions, muscle fibers suffer an imbalance in protein synthesis/degradation. This event causes muscle mass loss and decreased strength and muscle function, a syndrome known as sarcopenia. Recently, our laboratory described secondary sarcopenia in a chronic cholestatic liver disease (CCLD) mouse model. Interestingly, the administration of ursodeoxycholic acid (UDCA), a hydrophilic bile acid, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…BA profiling showed that lean NAFLD patients had lower levels of deoxycholic acid (DCA), glycodeoxycholic acid (GCDCA) and goosenodeoxycholic acid (CDCA), and higher levels of glycocholic acid (GCA) (3). Studies reported that serum cholic acid (CA), ursodeoxycholic acid (UDCA) and DCA impair muscle fiber structure and function and induce sarcopenia (138)(139)(140). And the level of CA is significantly higher in patients with severe fibrosis compared with those with none/mild fibrosis (3).…”
Section: Differential Metabolitesmentioning
confidence: 99%
“…BA profiling showed that lean NAFLD patients had lower levels of deoxycholic acid (DCA), glycodeoxycholic acid (GCDCA) and goosenodeoxycholic acid (CDCA), and higher levels of glycocholic acid (GCA) (3). Studies reported that serum cholic acid (CA), ursodeoxycholic acid (UDCA) and DCA impair muscle fiber structure and function and induce sarcopenia (138)(139)(140). And the level of CA is significantly higher in patients with severe fibrosis compared with those with none/mild fibrosis (3).…”
Section: Differential Metabolitesmentioning
confidence: 99%